Nonlinear Characteristics of Electrocardiograph Signals Based on Fractal (Xibei Gongye Daxue Xuebao, 2018)
In view of the nonlinear properties of Electrocardiograph (ECG) signal, the application of fractal methods from nonlinear system theory for the analysis of ECG signals has gained increasing interest.In this study, analysis of the objects are ECG signals of four sinus rhythms. Some important phenomena and conclusions have been captured and drawn after analyzing with and plotting the graphics of multi-fractal spectrum and auto-correlation functions. Additionally, the Hurst(H) parameters illustrate that self-similarity is a common property of the ECG signals, but the smaller H of the normal sinus rhythm(NSR) cause the obvious randomness of NSR. The further research of multi-fractal spectrum shows that the ECG signals all present local singular characteristics, but there are inconsistencies in the same type of sinus rhythm ECG signal. While, the inconsistency led to obvious classification, especially in NSR. As the conclusion, the results can be used as an effective complementary method for non-invasive diagnosis and early warning of heart disease.